The evolution of Devonian hydrocarbon gases in shallow aquifers of the northern Appalachian Basin: Insights from integrating noble gas and hydrocarbon geochemistry. (1st December 2015) - Darrah, Thomas H.; Jackson, Robert B.; Vengosh, Avner; Warner, Nathaniel R.; Whyte, Colin J.; Walsh, Talor B.; Kondash, Andrew J.; Poreda, Robert J.
Abstract: The last decade has seen a dramatic increase in domestic energy production from unconventional reservoirs. This energy boom has generated marked economic benefits, but simultaneously evoked significant concerns regarding the potential for drinking-water contamination in shallow aquifers. Presently, efforts to evaluate the environmental impacts of shale gas development in the northern Appalachian Basin (NAB), located in the northeastern US, are limited by: (1) a lack of comprehensive "pre-drill" data for groundwater composition (water and gas); (2) uncertainty in the hydrogeological factors that control the occurrence of naturally present CH4 and brines in shallow Upper Devonian (UD) aquifers; and (3) limited geochemical techniques to quantify the sources and migration of crustal fluids (specifically methane) at various time scales. To address these questions, we analyzed the noble gas, dissolved ion, and hydrocarbon gas geochemistry of 72 drinking-water wells and one natural methane seep all located ≫1 km from shale gas drill sites in the NAB. In the present study, we consciously avoided groundwater wells from areas near active or recent drilling to ensure shale gas development would not bias the results. We also intentionally targeted areas with naturally occurring CH4 to characterize the geochemical signature and geological context of gas-phase hydrocarbons in shallow aquifers of the NAB. Our data display a positive relationship between elevated [CH4 ], [C2 H6 ], [Cl], and [Ba] that co-occur with high [ 4 He]. Although four groundwater samples show mantle contributions ranging from 1.2% to 11.6%, the majority of samples have [He] ranging from solubility levels (∼45 × 10 −6 cm 3 STP/L) with below-detectable [CH4 ] and minor amounts of tritiogenic 3 He in low [Cl] and [Ba] waters, up to high [ 4 He] = 0.4 cm 3 STP/L with a purely crustal helium isotopic end-member ( 3 He/ 4 He = ∼0.02 times the atmospheric ratio ( R / Ra )) in samples with CH4 near saturation for shallow groundwater (P(CH4 ) = ∼1 atmosphere) and elevated [Cl] and [Ba]. These data suggest that 4 He is dominated by an exogenous (i.e., migrated) crustal source for these hydrocarbon gas- and salt-rich fluids. In combination with published inorganic geochemistry (e.g., 87 Sr/ 86 Sr, Sr/Ba, Br − /Cl − ), new noble gas and hydrocarbon isotopic data (e.g., 20 Ne/ 36 Ar, C2 +/C1, δ 13 C-CH4 ) suggest that a hydrocarbon-rich brine likely migrated from the Marcellus Formation (via primary hydrocarbon migration) as a dual-phase fluid (gas + liquid) and was fractionated by solubility partitioning during fluid migration and emplacement into conventional UD traps (via secondary hydrocarbon migration). Based on the highly fractionated 4 He/CH4 data relative to Marcellus and UD production gases, we propose an additional phase of hydrocarbon gas migration where natural gas previously emplaced in UD hydrocarbon traps actively diffuses out into and equilibrates with modern shallow groundwater (via tertiary hydrocarbon migration) following uplift, denudation, and neotectonic fracturing. These data suggest that by integrating noble gas geochemistry with hydrocarbon and dissolved ion chemistry, one can better determine the source and migration processes of natural gas in the Earth's crust, which are two critical factors for understanding the presence of hydrocarbon gases in shallow aquifers.